PENGARUH KOMITE AUDIT, LEVERAGE, DAN LIKUIDITAS TERHADAP AGRESIVITAS PAJAK - Elsa Selviana, (2021)
This study aims to examine the effect of audit committee, leverage, and liquidity on tax aggressiveness. This study also uses firm size and return on assets as control variables. Tax aggressiveness as dependent variable is proxied by Book Tax Different (BTD). Audit committee as an independent variable is measured using the proportion of audit committee members who have educational background in accounting or finance. Leverage is measured by Debt to Total Assets. Liquidity is measured by Current Ratio. The sample in this study amounted to 231 samples from 77 manufacturing companies listed on the Indonesia Stock Exchange during the 2017-2019 period. The analysis technique used is panel data regression analysis using STATA 14.2. The results of this study indicate that the audit committee does not have a significant effect on tax aggressiveness. While leverage and liquidity have a negative and significant effect on tax aggressiveness